The expression, purification and characterization of escherichia coli NudL, a putative coenzyme A hydrolase - Kellow-Webb, Sarah Maggie (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.